2019
DOI: 10.3390/medicina55110712
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Patients with Allergic Rhinitis to Ragweed Pollen in Two Distinct Regions of Romania

Abstract: Background and objectives: Ragweed pollen is a major source of allergen, which has rarely been observed in Romania until now. In this study, we evaluated the symptoms and associated factors in patients with allergic rhinitis to ragweed pollen in two distinct regions of Romania. Materials and Methods: We evaluated the records of patients newly diagnosed with allergic rhinitis induced by ragweed pollen in two allergological centers from North-West (NW) and Central parts of Romania between 2013 and 2015. The pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
(43 reference statements)
2
8
0
Order By: Relevance
“…Some scholars believe that allergic inflammation is not limited to the site where it initially occurs, and can be secondary to non-allergic reactions throughout the body (11). A number of reports have indicated that if not treated in time, allergic rhinitis can be complicated with asthma, sinusitis, otitis media, pharyngitis, conjunctivitis, and other diseases (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars believe that allergic inflammation is not limited to the site where it initially occurs, and can be secondary to non-allergic reactions throughout the body (11). A number of reports have indicated that if not treated in time, allergic rhinitis can be complicated with asthma, sinusitis, otitis media, pharyngitis, conjunctivitis, and other diseases (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients addressed to our center almost doubled from one year to another. Another recent study comparing clinical data of patients allergic to ragweed pollen from two other big Romanian cities, confirms the increasing number of affected persons from many of the country’s regions [ 39 ].…”
Section: Resultsmentioning
confidence: 83%
“…3 On the other hand, many investigators noticed association between ragweed sensitization and the recurrence of flare ups of AR and BA in adults and elderly 19,20,21 and the response to conventional therapy was limited. 22,23 In conclusion, ragweed sensitization seems common among school-age Egyptian children with bronchial asthma. However, sensitization with ragweed did not seem to increase the risk of flare ups or severity of asthma or to influence the choice of therapeutic modalities.…”
Section: Discussionmentioning
confidence: 85%